2011
DOI: 10.1053/j.gastro.2011.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Independent Changes in Blood Glucose Homeostasis After Gastric Bypass or Vertical Sleeve Gastrectomy in Rats

Abstract: Background & Aims Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG) reduce weight and improve glucose metabolism in obese patients, although it is not clear if metabolic changes are independent of weight loss. We investigated alterations in glucose metabolism in rats following RYGB or VSG. Methods Rats underwent RYGB or VSG and were compared to sham-operated rats that were fed ad lib or pair-fed with animals that received RYGB. Intraperitoneal glucose tolerance and insulin sensitivity tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
220
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(257 citation statements)
references
References 25 publications
32
220
1
4
Order By: Relevance
“…Our findings thus challenge the conventional ''hindgut'' hypothesis. On the contrary, consistent with previous reports, (8,32,33), SG resulted in a fourfold increase in postprandial GLP-1 ( Figure 3D) in this study, therefore supporting a role of FIGURE 4 Postoperative plasma levels of total GIP, PYY, total ghrelin and glucagon during OGTT. (A,B) SG dramatically increased glucosestimulated GIP and PYY (**P < 0.01) and reduced fasting ghrelin levels (C) (**P < 0.01).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings thus challenge the conventional ''hindgut'' hypothesis. On the contrary, consistent with previous reports, (8,32,33), SG resulted in a fourfold increase in postprandial GLP-1 ( Figure 3D) in this study, therefore supporting a role of FIGURE 4 Postoperative plasma levels of total GIP, PYY, total ghrelin and glucagon during OGTT. (A,B) SG dramatically increased glucosestimulated GIP and PYY (**P < 0.01) and reduced fasting ghrelin levels (C) (**P < 0.01).…”
Section: Discussionsupporting
confidence: 92%
“…Bariatric surgery causes durable weight loss, remission or improvement of type 2 diabetes, hypertension, dyslipidemia, sleep apnea, and reduction of cardiovascular disease and death (3)(4)(5)(6). Although weight reduction might in theory explain improvement of insulin resistance and associated conditions, studies in rodents (7)(8)(9) and humans (10,11) showed that the anti-diabetes effect of certain bariatric procedures, particularly gastric bypass surgery, results from mechanisms at least in part independent of weight loss (12)(13)(14).Understanding the mechanisms of action of surgery provides an opportunity to elucidate the pathophysiology of obesity and diabetes and may lead to the development of new treatments of curative intent.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, gastric bypass results in dramatically and rapidly enhanced meal-stimulated GLP-1, independent of weight loss and calorie restric- tion, likely from more direct nutrient exposure to intestinal L-cells (45). Furthermore, antagonism of the GLP-1R following Roux-en-Y gastric bypass (RYGB) worsens glucose tolerance and postprandial insulin secretion (46). Additionally, responsiveness to GLP-1R agonism in rodents was able to predict improvements in glycemic control following bariatric surgery, independent of weight loss (47).…”
Section: Glp-1 Action In the Gutmentioning
confidence: 99%
“…A major hypothesis is that changes in gut hormone release are crucial. Drastically increased postprandial circulating levels of GLP-1 and PYY have been demonstrated in clinical studies (18,32,33,36,38,44,47,50) and in rodent models (13,16,37,56) for both Roux-en-Y gastric bypass and vertical sleeve gastrectomy.…”
mentioning
confidence: 95%